Strategi Pengembangan Pembelajaran Silabus Akuntansi Keperilakuan di Perguruan Tinggi di Masa Pademi Covid 19 - Rinto Noviantoro; Yun Fitriano; Karona Cahya Susena; Mochammad Fahlevi (UNIVED Press, 2022)
This study aims to develop a behavioral accounting syllabus development strategy for students in the accounting study program. The syllabus on behavioral accounting at universities during the COVID-19 pandemic has been compiled with the latest behavioral accounting syllabus. This research was conducted by conducting in - depth interviews with participants who have expertise in behavioral accounting . This study describes behavioral accounting consisting of behavioral accounting understanding, behavioral characteristics, behavioral actions. During the COVID-19 PADEMI period, excellent health is needed, maintaining health protocols and has been vaccinated against covid 19 with two vaccinations registered in protected care, online learning such as using zoom media, Google class room or a hybrid where there is online and face-to-face learning by keeping a distance in class with no more than 50% of students in class so that they can study and maintain health.